SOME PROPERTIES OF PHOSPHORIC ACID STABILISED LATERIZED ADOBE BRICKS (Malaysian Journal of Civil Engineering, 2020)
The changes in the compressive strength of laterized bricks produced from stabilised residual tropical laterite (RTL) are reported in this paper. The RTL was stabilised with different percentages (2, 4, 6 and 8%) by weight of dry soil of 1M phosphoric acid (PA). Some geotechnical properties and elemental oxide composition of the RTL were determined. Adobe bricks were produced from the PA stabilised, 5% cement stabilised and unstabilised RTL. Adobe bricks produced from 5% cement stabilised RTL served as the control. The bricks were cured under ambient air condition for 7, 14, 21 and 28 days. The pH, dry density, moisture content and compressive strength (fc) of the bricks were determined at the end of each curing period. The influence of PA was evaluated using the changes in the fc of the adobe bricks. The effectiveness of PA was also evaluated using a standard minimum requirement. Statistical analysis of the results was done using Analysis of variance. There was about 90 and 200% increase in fc of PA and cement stabilised Adobe bricks, respectively. The fc of 6% PA stabilised and cement stabilised adobe bricks met the minimum requirement. It is concluded that PA has great potential for stabilising Adobe bricks for building.